The occurrence of PAHs and flame-retardants in air and dust from Australian fire stations. Issue 2 (3rd March 2020) - Banks, Andrew P. W; Engelsman, Michelle; He, Chang; Wang, Xianyu; Mueller, Jochen F.
Abstract: Firefighters are exposed to a wide range of chemicals whilst on duty, including polycyclic aromatic hydrocarbons (PAHs), organophosphate flame-retardants (OPFRs), and polybrominated diphenyl ethers (PBDEs). These groups of chemicals are related to combustion emissions. PAHs are formed during combustion. OPFRs and PBDEs are flame-retardants and are inadvertently released during combustion. Exposure to these chemicals occurs when attending fire scenes, and firefighters can track these chemicals back into fire stations leading to further exposure. The objective of this study was to understand the concentrations of PAHs, OPFRs, and PBDEs in fire stations, to evaluate factors that affect chemical concentration, and to assess how air and dust could contribute to firefighters' relevant exposure risk. Concentrations of 13 PAHs, 9 OPFRs, and 8 PBDEs were quantified in fire station dust (n = 49) and air (n = 15) samples collected between November 2017 and February 2018. The median ∑13 PAH concentration was 15 ng m −3 and 3.1 µg g −1 in air and dust, respectively, while the median ∑9 OPFR concentration was 56 ng m −3 in air and 84 µg g −1 in dust, and ∑8 PBDE had a median concentration of 0.78 ng m −3 in air and 26 µg g −1 in dust. The estimated daily intakes through dust and air for ∑13 PAHs, ∑9 OPFRs, and ∑8 PBDEs in firefighters were 3.6, 17, and 1.6 ng (kg body weight) −1  day −1, respectively. The worst-case estimated daily intakes were only 2% of the reference dose for individual chemicals. Pearson's correlations with chemical concentration for several PAHs, OPFRs, and PBDEs were found between the number of years since fire stations were last renovated, as well as the storage locations of firefighting ensembles. These results suggest chemicals are brought back to fire stations from fire scenes and that they are accumulating in fire stations. They also suggest soiled firefighting ensembles are a source of these chemicals in fire stations and that their proximity to the rest of the station determines the extent to which they contribute to chemical concentrations in fire stations.